PEMBUATAN APLIKASI PENENTUAN TINGKAT KEMIRIPAN ANTAR DOKUMEN TEKS MENGGUNAKAN METODE VECTOR SPACE MODEL - Alfine Candra Cuaca; Lely Hiryanto; Tri Sutrisno (Jurnal Ilmu Komputer dan Sistem Informasi, 2018)
The application of similarity detection between text documents created using Vector Space Model (VSM) method gives result of similarity degree values and percentage of similarity between comparison document and the test documents. The process of this method, first calculates the word weight with pre-processing that is using Term Frequency – Inverse Document Frequency (TF-IDF), then calculates the dot product between comparison documents with each test document and dot product document with the document itself, then to calculate the angle using cosine similarity to get the similarity degree values between the comparison documents with each test document.The test is done by using data from the students of Faculty of Information Technology, Tarumanagara University amounted to 21 people which divided into 4 sections, namely chapter I, chapter III, chapter IV, and chapter V. The test results showed that the application can operate the VSM method well and in the testing process, VSM method is not affected by the length of the documents and also not affected by the word order.